Expression of IL-20 Receptor Subunit β Is Linked to EAE Neuropathology and CNS Neuroinflammation - Dayton, Jacquelyn R.; Yuan, Yinyu; Pacumio, Lisa P.; Dorflinger, Bryce G.; Yoo, Samantha C.; Olson, Mariah J.; Hernández-Suárez, Sara I.; McMahon, Moira M.; Cruz-Orengo, Lillian (Frontiers in Cellular Neuroscience, 2021)
Considerable clinical evidence supports that increased blood–brain barrier (BBB) permeability is linked to immune extravasation of CNS parenchyma during neuroinflammation. Although BBB permeability and immune extravasation are known to be provoked by vascular endothelial growth factor-A (i.e., VEGF-A) and C-X-C motif chemokine ligand 12 (CXCL12), respectively, the mechanisms that link both processes are still elusive. The interleukin-20 (i.e., IL-20) cytokine signaling pathway was previously implicated in VEGF-mediated angiogenesis and is known to induce cellular response by way of signaling through IL-20 receptor subunit β (i.e., IL-20RB). Dysregulated IL-20 signaling is implicated in many inflammatory pathologies, but it’s contribution to neuroinflammation has yet to be reported. We hypothesize that the IL-20 cytokine, and the IL cytokine subfamily more broadly, play a key role in CNS neuroinflammation by signaling through IL-20RB, induce VEGF activity, and enhance both BBB-permeability and CXCL12-mediated immune extravasation. To address this hypothesis, we actively immunized IL-20RB–/– mice and wild-type mice to induce experimental autoimmune encephalomyelitis (EAE) and found that IL-20RB–/– mice showed amelioration of disease progression compared to wild-type mice. Similarly, we passively immunized IL-20RB–/– mice and wild-type mice with myelin-reactive Th1 cells from either IL-20RB–/– and wild-type genotype. Host IL-20RB–/– mice showed lesser disease progression than wild-type mice, regardless of the myelin-reactive Th1 cells genotype. Using multianalyte bead-based immunoassay and ELISA, we found distinctive changes in levels of pro-inflammatory cytokines between IL-20RB–/– mice and wild-type mice at peak of EAE. We also found detectable levels of all cytokines of the IL-20 subfamily within CNS tissues and specific alteration to IL-20 subfamily cytokines IL-19, IL-20, and IL-24, expression levels. Immunolabeling of CNS region-specific microvessels confirmed IL-20RB protein at the spinal cord microvasculature and upregulation during EAE. Microvessels isolated from macaques CNS tissues also expressed IL-20RB. Moreover, we identified the expression of all IL-20 receptor subunits: IL-22 receptor subunit α-1 (IL-22RA1), IL-20RB, and IL-20 receptor subunit α (IL-20RA) in human CNS microvessels. Notably, human cerebral microvasculature endothelial cells (HCMEC/D3) treated with IL-1β showed augmented expression of the IL-20 receptor. Lastly, IL-20-treated HCMEC/D3 showed alterations on CXCL12 apicobasal polarity consistent with a neuroinflammatory status. This evidence suggests that IL-20 subfamily cytokines may signal at the BBB via IL-20RB, triggering neuroinflammation.